2013
DOI: 10.33687/phytopath.002.01.0023
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Races and Virulence Diversity of Puccinia graminis pers. f. sp. tritici eriks. & e. Henn. on Wheat in Tigray Region of Ethiopia

Abstract: Wheat stem rust caused by Puccinia graminis f. sp. tritici is a disease that causes complete annihilation of wheat crops over wide areas during epidemic years. The highland of Ethiopia is considered as a hot spot area for the development of stem rust complex. Hence, this study was carried out to detect the virulence diversity of P. graminis f. sp. tritici in Southern Tigray. The findings of this paper were based on race analysis through inoculation of stem rust populations, isolation and multiplication of sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Studies carried out in Ethiopia showed that most previously identified races such as TTKSK, TKTTF, TTTTF, TRTTF, RRTTF, and others were virulent on most varieties grown in the country [ 38 ]. Accordingly, many field evaluation studies for Pgt response have been carried out in different wheat-growing regions of the country [ 22 , 39 , 40 ]. Most elite breeding lines skewed towards moderate resistance, although some differences were observed between individual genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in Ethiopia showed that most previously identified races such as TTKSK, TKTTF, TTTTF, TRTTF, RRTTF, and others were virulent on most varieties grown in the country [ 38 ]. Accordingly, many field evaluation studies for Pgt response have been carried out in different wheat-growing regions of the country [ 22 , 39 , 40 ]. Most elite breeding lines skewed towards moderate resistance, although some differences were observed between individual genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Yield losses in wheat by leaf rust in cultivar trials were also reported in Mississippi, USA [15]. Due to heavy infection of leaf rust, growth and yield parameter of wheat plants are adversely affected [16,17].…”
Section: Introductionmentioning
confidence: 98%